Platelet-Rich Plasma Induces Autophagy and Promotes Regeneration in Human Dental Pulp Cells - Xu, Hanxin; Xu, Fen; Zhao, Jiajia; Zhou, Caixia; Liu, Jiarong (Frontiers in Bioengineering and Biotechnology, 2021)
Regenerative endodontic procedures using autologous platelet rich plasma (PRP) can improve the biologic outcome of treatment. However, its mechanism of action on improving pulp regeneration is not fully elucidated. Autophagy was recently shown to be related to tissue repair and osteogenesis. Therefore, the objective of this study was to investigate the effect of PRP in dental pulp regeneration and to elucidate the role of autophagy involved in this process. Human dental pulp cells (hDPCs) were isolated from healthy dental pulp and co-cultured with an increasing concentration of PRP. Cellular migration and proliferation were determined by scratch assay, transwell assay and cell-counting kit 8 assay. Osteogenic differentiation was clarified by using alkaline phosphatase staining, alizarin red staining and real-time polymerase chain reaction to measure the gene expression levels of alkaline phosphatase, collagen-1, osteocalcin, dentin matrix protein 1 and dentin sialophosphoprotein. Autophagic bodies were observed by transmission electron microscopy and the expression of autophagy marker light chain 3B (LC3B) was determined by immunofluorescence staining. The effect of PRP on cellular migration, proliferation and osteogenic differentiation was further investigated in the milieu of autophagy activator, rapamycin and inhibitor, 3-methyladenine. Results showed that PRP promoted cell migration, proliferation and osteogenic differentiation. Autophagic bodies were strongly activated and the protein expression of LC3B was significantly promoted by PRP. Autophagy inhibition suppressed PRP-induced hDPCs migration, proliferation and osteogenic differentiation, whereas autophagy activator substantially augmented PRP-stimulated migration, proliferation and differentiation. Taken together, these findings suggested that PRP could effectively promote regenerative potentials associated with autophagy.